Rancang Bangun Kontrol Air Conditioner Otomatis Menggunakan Algoritma Propotional Integral Derivative (PID) Berbasis Internet of Things - Sinaga, Putri; Enri, Jon; Handayani, Ade Silvia (Forum Kerjasama Pendidikan Tinggi, 2024)
An efficient and responsive air conditioning control system is essential for maintaining thermal comfort as well as energy efficiency in a room. This research develops an AC control system based on the number of people entering or leaving the room using the PID (Proportional-Integral-Derivative) algorithm integrated with Internet of Things technology through the Blynk platform. Infrared proximity and temperature sensors are used to detect the number of people in the room and measure the room temperature. This data is then processed by the ESP32 microcontroller which runs the PID algorithm to generate a control signal that will adjust the AC temperature towards the setpoint. This system allows the AC temperature to be dynamically adjusted based on changes in the number of people in the room, which is expected to optimize energy consumption. In addition, integration with Blynk allows real-time monitoring and control of the system through a smartphone app, providing users with greater flexibility and control. The trial results show that the system is able to respond to changes in the number of people and maintain the room temperature within comfortable limits (setpoint). As such, it offers an effective solution for smarter room temperature management.